Odpowiedzi

2013-08-14T21:22:31+02:00
A)
4x + y = 11
5y - x = 13  /*4

4x + y = 11
-4x + 20y = 52
21y = 63  /:21
y = 3

4x + 3 = 11
4x = 11 - 3
4x = 8  /:4
x = 2

x = 2
y = 3

układ oznaczony

b)
2x + 5 = 7y
2(x + 2) - 7y = -1

2x - 7y = -5
2x + 4 - 7y = -1

2x - 7y = -5
2x - 7y = -5  /*(-1)

2x - 7y = -5
-2x + 7y = 5
0 = 0
Układ nieoznaczony

c)
3(x + y) - 2(y + 3) = y + 3(x - 2)
x - 2y = 5

3x + 3y - 2y - 6 = y + 3x - 6
x - 2y = 5

3x + y - y - 3x = -6 + 6
x - 2y = 5

0 = 0
x - 2y = 5
układ nieoznaczony

d)
2x + 5y = 2
3(x + y) + 2y = 3

2x = 5y = 2
3x + 3y + 2y = 3

2x + 5y = 2
3x + 5y = 3  /*(-1)

2x + 5y = 2
-3x - 5y = -3
-x = -1  /:(-1)
x = 1

2 * 1 + 5y = 2
5y = 2 - 2
5y = 0  /:5
y = 0
układ oznaczony
1 5 1